Electronic spectroscopy of toluene-rare-gas clusters: the external heavy atom effect and vibrational predissociation. - Doyle, R; Love, E; Da Campo, R; Mackenzie, S (2005)
Toluene-X van der Waals clusters (where X = Ne, Ne2, Ar, Ar2, Kr, Xe) have been investigated by fluorescence excitation spectroscopy in the region of the S1-S0 transition. With the exception of Xe, for each rare-gas studied, we have assigned cluster transitions in the region of all the strong monomer vibrational bands up to 1000 cm(-1) above the origin band. We have further investigated the S1 relaxation dynamics for each vibrational level of each complex, via their fluorescence decay profiles. Clustering with neon has little appreciable effect on the vibrationless S1 lifetime. By contrast, the clusters with argon and krypton exhibit markedly shorter fluorescence lifetimes compared with the monomer. The effect is so severe in the case of toluene-Xe clusters that no fluorescence signals were observed. We interpret these results in terms of an external heavy atom effect in which the rate of intersystem crossing in toluene is influenced by the cluster partner. For clusters built upon excited S1 vibrational levels, the situation is potentially complicated by intramolecular vibrational redistribution and vibrational predissociation (VP). The majority of the fluorescence decay profiles were satisfactorily modeled using single exponential decays. The emission following pumping of the 37(1) level in the toluene-Kr cluster, however, is an exception. We have modeled the decay of this level with a simple kinetic scheme including VP and determined a predissociation rate of (1.04 +/- 0.54) x 10(7) s(-1).